Guidelines for Managing the Learning Ecosystem towards Desired Outcomes of Learners in Basic Education - Samyong, Radchadaporn; Manokarn, Monnapat; Damrongpanit, Suntonrapot (Dhammathas Academic Journal, 2024)
The purposes of this research were 1) to synthesize and confirm the components of the learning ecosystem, 2) to study the processes and best practices in managing the learning ecosystem, and 3) to develop and validate management guidelines for the learning ecosystem. The sample group consisted of 500 participants, administrators and teachers affiliated with the Basic Education Commission. The research tools included questionnaires on perceptions of the learning ecosystem components, with an Item Objective Congruence (IOC) value between 0.80 and 1.00, with a reliability value 0.969. Data were collected through questionnaires, analyzed using Mplus software for confirmatory factor analysis, and supplemented with qualitative data gathered from interviews with 7 qualified individuals. Additionally, focus group discussions with 7 qualified individuals were conducted to validate the management guidelines for the learning ecosystem. And interviews to explore management guidelines. Analyze data used content analysis. The results revealed that: 1. The learning ecosystem comprised five components: 1) educational policies and strategies, 2) learning content, 3) personnel, 4) learning culture, and 5) learning resources. 2. Effective management of the learning ecosystem requires promoting and supporting four main areas: 1) reasons/motivations contributing to system development, 2) management processes, 3) success conditions affecting system management, and 4) recommendations. 3. Management guidelines for achieving desired learning outcomes encompass 5 main aspects: 1) principles, 2) objectives, 3) methods/processes, 4) success conditions, and 5) recommendations. Overall, the validation of these guidelines demonstrated high levels of suitability, feasibility, and utility.